The Relationship between Knowledge and Attitudes of Adolescents and Perceptions of HIV/AIDS Transmission at State Senior High School 06 Mandau, Bengkalis Regency, Riau Province in 2024 - Willhelmina Wahara; Sartika, Dewi (PT Inovasi Pratama Internasional, 2025)
HIV/AIDS is a disease that has received significant attention from various parties. Indonesia is one of the countries experiencing a significant increase in cases. However, Indonesia is still lagging behind in achieving the global target of HIV control, namely 95-95-95. As of December 2022, the first 95 percent achievement is still at 81%; for the second 95 percent, the achievement is still less than half (41%) who are still on ARV treatment; the third 95 percent achievement is only 19% of PLHIV on ARV treatment whose viruses are suppressed. This study was conducted to determine the relationship between knowledge and attitudes of adolescents at SMA Negeri 06 Mandau regarding HIV/AIDS in 2024. This study was conducted cross-sectionally by administering questionnaires to students of SMA Negeri 06 Mandau from May to September 2024. The sample was taken by total sampling from the population at SMA Negeri 06 Mandau. Of the 55 students who were respondents in this study, 5 people (9.1%) had good knowledge, 24 people (43.6%) had sufficient knowledge, and 26 people (47.3%) had insufficient knowledge. Based on the results of the chi square test of the relationship between adolescent knowledge and HIV/AIDS transmission in SMA Negeri 06 Mandau in 2024, with a degree of significance (α) = 0.1 and df = 1, the calculation results were obtained based on a significance value <0.05, then Ho was rejected and if the significance value> 0.05, then Ho was accepted because the significance value <0.05 (0.000 <0.05) then Ho was rejected, meaning there was a relationship between adolescent knowledge and HIV/AIDS transmission in SMA Negeri 06 Mandau, Bengkalis Regency, Riau Province in 2024. The conclusion of this study is to increase knowledge and information among adolescents about the perception of HIV/AIDS transmission in SMA Negeri 06 Mandau, Bengkalis Regency, Riau Province.